THE EFFECTIVITY OF RAW EXTRACT GUAVA LEAF IMMUNOSTIMULANT (Psidium guajava) ON LIVER HISTOPATHOLOGY OF PATIN (Pangasius sp.) TESTED THE CHALLENGE Aeromonas hydrophila BACTERIA - Rahman, Ihsan Sanggar; Maftuch, Mr.; Sanoesi, Ellana (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2018)
The purpose of this study described the influence and the dose of guava leaf raw extract (P. guajava) as an immunostimulant towards liver histotapologi Patin (Pangasius sp.) Challenge tested A. hydrophila bacteria. This study uses a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments used was of guava leaf extract doses A dose of 2% (2.4 g / 120 g), and 4% (4.8 g / 120 g), C 6% (7.2 g / 120 g) and K without a guava leaf extract and tested bacteria A. hydrophila challenge. Based on the results obtained in the study of liver histopathology Patin (Pangasius sp.), there was damage Inflammation and necrosis of the liver tissue in order from the most severe damage to the least obtained at treatment K (0%) 3,07, A ( 2%) 2.53, B (4%) of 2.33, and the best treatment is C (6%) with an average damage of 1.67. Necrosis of liver tissue damage in a sequence of severe damage to the least, namely the treatment of K (0%) 2,67, A (2%) 2.33, B (4%) 2.20, and C (6%) 1,53. Lowest average gained in treatment C (6%). The results showed that the dose can reduce the level of tissue damage that was at a dose of 6% (7.2 g / 120 g). The best dose is 6% (7.2 g / 120 g), which can reduce the level of damage indicate the level of tissue damage smaller percentage of damage 6-25%.